External Patch Fillet Repair For Sulphur Recovery Unit Of Petroleum Refinery Plant - Abdul Munir, Fudhail; Ridzuan Tan, Nurfarah Diana; Abdul Rahman, Abdul Razak; Ariffin, Eddy Azrai; Saputro, Herman (Universiti Malaysia Perlis, 2020)
The main function of Sulphur Recovery Unit (SRU) is to recover 99.2% of sulphur from the feed of Amine Regeneration Unit (ARU) and Sour Water Treating Unit (SWTU). Hotspot related problem or localized burning can be detrimental to the SRU material lifespan. One of the causes of the hotspot is susceptible high vibration level of multi-components in SRU. Downing of SRU in any refinery plant leads to unplanned losses in revenue. Thus, thorough routine maintenance needs to be performed to avoid such disruption. In this project, the method of repairing part of the SRU reheater external wall is presented. External patch fillet is introduced to seal the damaged reheater external shell wall. Before the maintaining process, the root cause of the problem is first examined. Fitness for service (FFS) is also performed to ensure that the repair method is sufficient for continuous operation. The obtained results from the assessments were used to conduct the required repair services. All assessment and repair methods are based on the guidelines set by the relevant codes and standards.